2018
DOI: 10.21315/tlsr2018.29.1.9
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Microalgae as Live Food for Brachionus plicatilis (Rotifer) in Intensive Culture System

Abstract: Brachionus plicatilis is used to feed fish and crustacean larvae in the aquaculture industry. It is well established that the type of microalgae may influence rotifer production. This experiment was conducted to determine the effect of five different locally available microalgae species at Fisheries Research Institute (FRI), Kampung Pulau Sayak, Kedah, Malaysia on the instantaneous growth rate (μ) of rotifer. Nannochloris sp., Tetraselmis sp., Isochrysis sp., Chlorella sp., and Nannochloropsis sp. were used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…For instance, tryptophan was absent, whereas cysteine and methionine might have been underestimated. This was due to the destructive effect of acid hydrolysis (Brown, ; Rahman et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, tryptophan was absent, whereas cysteine and methionine might have been underestimated. This was due to the destructive effect of acid hydrolysis (Brown, ; Rahman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Microalgae have high potential application values in animal nutrition and agriculture sectors as sources of proteins, lipids, vitamins, minerals and pigments, plus the carbon-neutral benefits from CO 2 fixation for alleviating greenhouse gas (GHG) discharge (Brune, Lundquist, & At present, more than 40 species of microalgae have been used as a source of fodder as live or dead cells to improve the properties of aquatic animals, such as fish, mussels and shrimp (Lubzens & Zmora, 2003;Pulz & Gross, 2004;Rahman et al, 2018). Legal restrictions or bans on antibiotic administration in aquaculture encourage the development of environmentally friendly feed additives as immunostimulants (Hoseinifar, Sun, & Caipang, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otro estudio mostró que mezclas de B. subtilis, B. licheniformis, B. megaterium y B. laterosporous (10 8 UFC L -1 c/u) tienen un efecto directo sobre la fecundidad de los rotíferos (eggratios de 0,30 a las 48 h de tratamiento) (Zink et al, 2013). En concordancia, los datos del presente estudio sugieren un notable efecto de Bacillus firmus C101 sobre el crecimiento poblacional, fecundidad y productividad de B. plicatilis s.s., cuando se administra a una dosis de 10 6 UCF mL -1 , después de 48 h. No obstante, comparaciones directas de la dinámica poblacional entre estudios de rotíferos puede ser complicado debido a la utilización de diferentes cepas, mezclas, mecanismos de suministro y/o condiciones previas o durante el cultivo como el tipo, y cantidad de microalgas suministradas como alimento primario (Snell et al, 1983;Abd Rahman et al, 2018).…”
Section: Evaluation Of B Firmus C101 As a Probiotic For Rotifersunclassified
“…Another study showed that mixtures of B. subtilis, B. licheniformis, B. megaterium and B. laterosporous (10 8 CFU L -1 each) have a direct effect on the fecundity of rotifers (egg-ratios from 0.30 to 48 h of treatment) (Zink et al, 2013). In agreement, the data of the present study suggest a remarkable effect of Bacillus firmus C101 on population growth, fertility, and productivity of B. plicatilis s.s., when administered at a dose of 10 6 UCF mL -1 , after 48 h. However, direct comparisons of population dynamics between studies of rotifers can be complicated due to the use of different strains, mixtures, delivery mechanisms, and/or preconditions or during cultivation as the type, and quantity of microalgae supplied as a primary food (Snell et al, 1983;Abd Rahman et al, 2018).…”
Section: Evaluation Of B Firmus C101 As a Probiotic For Rotifersmentioning
confidence: 99%